Revisiting the systematics of the Ranitomeya uakarii complex (Anura: Dendrobatidae) with the description of a new species from the Fitzcarrald Arch of Peru and Brazil - Brown, Jason L.; Geralds, Breann; Moraes, Leandro J. C. L.; Granados-Martínez, Sofía; May, Rudolf Von; Muell, Morgan R.; Guillory, Wilson X.; Twomey, Evan (Zootaxa, 2026)
A new species of Ranitomeya from Amazonian lowland forests in western Brazil and southeastern Peru is described and named. This species was formerly considered to be an outlying population of R. uakarii on the southern periphery of its distribution. We analyze new and existing phylogenomic data and infer that the new species is not part of nor closely related to R. uakarii, but is sister to a clade including R. benedicta and a lineage referred to here as R. aff. benedicta. The new species can be distinguished from all other Ranitomeya by its distinctive color pattern, with thin yellow stripes on the dorsum, complete dorsolateral stripes, a complete labial stripe, and a single middorsal stripe that extends from the vent, forks into two stripes anterior to the orbital sockets and merges with dorsolateral stripes, forming a large yellow ring on the top of snout. There are four Ranitomeya species that look similar and co-occur in the general distribution of the new species (R. hwata, R. sirensis, R. variabilis, and R. toraro). The new species can be distinguished from all of them by the combination of a complete middorsal stripe and a round black rostral spot. Given the few and temporally scattered known records, the new species appears to be naturally rare, which raises concern regarding its conservation status.